2018
DOI: 10.1073/pnas.1715492115
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in axonogenesis genes connect three families with sound–color synesthesia

Abstract: SignificanceOur physical senses are separated not only into distinct experiences but also into specialized regions within the cerebral cortex. Synesthesia is a neurological phenomenon that causes unusual links between sensory experiences, and its molecular basis is completely unknown. We demonstrate that three families who experience color when listening to sounds are connected by rare genetic variants affecting genes that contribute to axonogenesis, a process essential for neuronal connections within and acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
1
44
0
1
Order By: Relevance
“…We propose that genetically determined differences in synaesthetes (e.g. increased connectivity [14]) do not cause grapheme-colour associations per se, but instead cause existing, environmentally influenced grapheme-colour associations to be strengthened and 'locked in': made stable over time. As a result of this 'locking in' mechanism, synaesthetes, when asked to report a grapheme-colour association for an experiment, will report an association that was formed at a specific moment in development.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We propose that genetically determined differences in synaesthetes (e.g. increased connectivity [14]) do not cause grapheme-colour associations per se, but instead cause existing, environmentally influenced grapheme-colour associations to be strengthened and 'locked in': made stable over time. As a result of this 'locking in' mechanism, synaesthetes, when asked to report a grapheme-colour association for an experiment, will report an association that was formed at a specific moment in development.…”
Section: Introductionmentioning
confidence: 97%
“…Synaesthesia is thought to be related to excess connectivity between brain regions, and brain imaging studies have found both structural and functional brain connectivity differences between synaesthetes and controls ( [4][5][6][7][8]; for a review, see [9]). Synaesthesia tends to run in families: 42% of synaesthetes report a first-degree relative with synaesthesia ( [10]; see [11] for a review) and studies suggest that the propensity to develop synaesthesia is partly, but not completely, attributable to genetics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The precise nature of these factors is poorly understood, but it is thought that several mechanisms are involved, ranging from rare DNA variants with large effects (more akin to monogenic inheritance) to combined actions of common polymorphisms, each with only a small effect on the trait. Investigations of families where multiple relatives are synaesthetic indicate that, even where rare variation could be responsible, there is substantial genetic heterogeneity, meaning that distinct genetic loci may be involved in different families [5][6][7][8][9]. Against this background, we previously performed a whole-exome sequencing study and found enrichment of rare variants in genes associated with axonogenesis in three families with sound-colour synaesthesia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of families where multiple relatives are synaesthetic indicate that, even where rare variation could be responsible, there is substantial genetic heterogeneity, meaning that distinct genetic loci may be involved in different families [5][6][7][8][9]. Against this background, we previously performed a whole-exome sequencing study and found enrichment of rare variants in genes associated with axonogenesis in three families with sound-colour synaesthesia [9]. These results supported a long-standing hypothesis that synaesthesia may be caused in part by altered or hyperconnectivity between brain regions processing the inducing and concurrent sensory stimuli [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…broaden our understanding of the molecular dysfunctions of distinct NHE6 variants associated with Christianson syndrome. _______________________________________ Genetic variants or aberrant expression of SLC9A6 (solute carrier family 9, member A6), an X chromosome gene encoding the alkali cation (Na + , K + )/proton (H + ) exchanger NHE6 isoform, have been linked to multiple neurological conditions, including Christianson syndrome (CS) , autism spectrum disorder (25,26), schizophrenia (25), chromesthesia (i.e., auditory-visual synesthesia) (27), idiopathic Parkinson's disease (28) and Alzheimer's disease (29,30). Evidence establishing a direct causal relationship between altered gene function and phenotype is strongest for CS, a debilitating neurodevelopmental disorder manifested in males by moderate to severe intellectual disability, autistic-like behaviour, epilepsy, microcephaly, mutism, hypotonia, sensory and motor dysfunction, neurodegeneration, and shortened lifespan (1,15).…”
mentioning
confidence: 99%